Prospective study on ectopic pregnancy in a tertiary care hospital - Ilanjselvi, M.; Priya, K. Shobana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pregnancy of unknown location was frequently missed and increasing incidence of ectopic pregnancy needs awareness about common risk factors, mortality and morbidity. Aim of this study is identify the incidence, clinical presentation, risk factors, treatment, mortality and morbidity associated with ectopic pregnancies. Methods: Prospective analysis of ectopic was done in Chengalpattu Government Medical College and Hospital from December 2018 to December 2019. Parameters included in this study was age, parity, gestational age, risk factors, clinical presentation, site of ectopic, need of blood transfusion, mode of management, mortality and morbidity were identified. Results: Out of 10900 deliveries, 53 were ectopic pregnancies (0.48%). Women with age 20-25 years had highest incidence (54.71%) and with least below 20yrs and above 40 years (1.88%). Ectopic pregnancies were common in multiparous women (70.68%) than primigravida (28.30%). Common symptoms: amennorhea (98.11%), pain abdomen (96.22%), bleeding per vaginum (47.16%) patients. Urine pregnancy test positive in 98.11%. Etiology was pelvic infection (18.88%), surgeries including LSCS and tubal surgeries (15.09%), previous dilatation and curettage was done in (15.09%) cases, previous ectopic (5.66%), intrauterine contraception usage seen in (1.88%). Right sided ectopic was more common. Site of ectopic: common in fallopian tube- ampullary region (54.71%)), fimbria (22.64%), isthumus (11.32%), followed by ovarian ectopic (5.66%) cornual (3.77%), caesarean scar (1.88%) tubal abortion (1.88%). About 94.33% of ectopic was ruptured, 3/4th of these patients presented with shock at the time of presentation. Most of cases being ruptured ectopic pregnancies, unilateral salpingectomy in 75.47% and unilateral salpingoopherectomy in 3.77%. Salpingectomy with contralateral tubal ligation done in 15.09%, laparoscopic salpingectomy done in 3.77%, hysterectomy done for 1.88%. Blood transfusion was done in (96.22%), without single mortality. Conclusions: Immediate prompt diagnosis, identifying the high-risk factors and early intervention by conservative or surgical management will help in reducing the mortality and morbidity associated with ectopic pregnancted.